A computational procedure for prediction of ballasted track profile degradation under railway traffic loading. (November 2016) - Nguyen, K; Villalmanzo, D I; Goicolea, J M; Gabaldon, F
A computational procedure is developed in the present paper, allowing the prediction of the ballasted track profile degradation under railway traffic loading. In this procedure, an integration of the short-term and long-term mechanical processes of track deterioration is taken into account, using a track degradation model. This degradation model is incorporated into a finite element code where two modes of calculation are implemented: the "implicit mode" concerns the short-term track deterioration, in which the hypoplastic model is used for the ballast layer and the dynamic response to an instantaneous train axle passage is obtained to serve as input data for the "explicit mode", which concerns the simulation of long-term track deterioration, using the accumulation model for ballast layer. The whole procedure is illustrated on the prediction of the ballasted track profile degradation of a track section of 100 m. The results show a significant influence of the type of track geometry defects and the vehicle velocity on the evolution of track deterioration and the capability of the proposed procedure in reproducing the track profile degradation.